2016
DOI: 10.1007/s00467-016-3389-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequential use of hemoperfusion and single-pass albumin dialysis can safely reverse methotrexate nephrotoxicity

Abstract: CHP and SPAD are effective extracorporeal methods of removing methotrexate. They provide alternative treatment options for critical care nephrologists in the management of methotrexate toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…From a physiological perspective, MTX has a volume of distribution of 0.4-0.8 L/kg, a molecular weight of 454 Daltons and a plasma protein binding of 50%, so extracorporeal renal support therapy has a favorable profile for MTX elimination. However, its use is subject to debate since there is a high level of MTX binding to plasma proteins; therefore, hemoperfusion (21), hemodialysis with high cut-off filters (22), or continuous renal support by means of continuous veno-venous hemofiltration have been proposed (23). These therapeutic options can be considered in addition to the previously mentioned medical management and in cases of persistently high MTX concentrations and multisystem involvement.…”
Section: Discussionmentioning
confidence: 99%
“…From a physiological perspective, MTX has a volume of distribution of 0.4-0.8 L/kg, a molecular weight of 454 Daltons and a plasma protein binding of 50%, so extracorporeal renal support therapy has a favorable profile for MTX elimination. However, its use is subject to debate since there is a high level of MTX binding to plasma proteins; therefore, hemoperfusion (21), hemodialysis with high cut-off filters (22), or continuous renal support by means of continuous veno-venous hemofiltration have been proposed (23). These therapeutic options can be considered in addition to the previously mentioned medical management and in cases of persistently high MTX concentrations and multisystem involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite fast efficacy and improved tolerance with less hypersensitivity reactions and charcoal embolization nowadays, since cellulose coated charcoal filters were introduced, and in parallel with the advance of hemodialysis techniques and availability of high efficacy filters, CHP has lost popularity ( 11 ). Decline in the use of CHP relies on the high cost of the columns, which become saturated and loose effectiveness during the treatment, and short expiration time.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis is a suitable method for low molecular weight, water soluble molecules. Larger size molecules, such as MTX, are insufficiently removed by standard HD and require high flux filters ( 11 ). High-flux hemodialysis is the most frequently implemented extracorporeal therapy in cases of MTX toxicity but efficacy is limited ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested and utilized KRT as a supportive treatment and shown improvement in multiple organ systems due to clearance of chemotherapeutic agents and constant control of fluid hemodynamics (Table 6). 65–69 In a retrospective analysis of cancer patients with varying etiologies of AKI, including nephrotoxic drugs, sepsis, and tumor lysis syndrome, CVVHDF was the most widely used KRT method (followed by CVVHD and CVVHF) with an overall hospital mortality rate of 63% 64 . Only 38 patients survived, but 20 of them had a complete resolution of AKI.…”
Section: Chemotherapy‐induced Nephrotoxicity and The Role Of Kidney Replacement Therapymentioning
confidence: 99%